Effects of the rise-to-span ratio on the progressive collapse resistance of Kiewitt-6 single-layer latticed domes. (December 2019) - Tian, Li-min; Li, Qi-bing; Zhong, Wei-hui; Wei, Jian-peng
Abstract: Kiewitt-6 (K6) single-layer latticed dome scale models with rise-to-span ratios of 1/8 and 1/6 were developed to evaluate their progressive collapse dynamics. For each dome, the structural responses, including the joint displacement and member strain of the remaining components, were recorded after four key members were abruptly removed in succession. The effects of the rise-to-span ratio on the progressive collapse resistance of the K6 single-layer latticed domes were examined after constructing and validating finite element (FE) models. The experiments and FE analysis yielded the following results: 1) K6-6 and K6-8 domes have identical collapse modes; the joint loads were transferred via surrounding localised arch action, and the collapse of the arch following member failure led to the progressive collapse of the latticed domes. 2) Compression mechanisms served to inhibit progressive collapse of the K6-6 and K6-8 domes. 3) For the K6-6 dome, there was a 1-s transient equilibrium state following the structural vibration prior to the final collapse; this transient state was not observed in the K6-8 dome. 4) The K6-6 dome collapsed more slowly and demonstrated better progressive collapse resistance than the K6-8 dome. 5) The progressive collapse resistance and steel consumption were optimised under the condition of a rise-to-span ratio of 1/5. Highlights: Progressive collapse tests of K6 domes with two rise-to-span ratios were conducted. Compression mechanism of K6 domes were proposed to resist progressive collapse. A transient equilibrium state prior to the final collapse was proposed and discussed. The balance between collapse resistance and steel consumption was analyzed.